CURAHAN KERJA WANITA UNTUK MENINGKATKAN PRODUKTIVITAS DAN KESEJAHTERAAN KELUARGA : STUDI PADA PETERNAK SAPI PERAH RAKYAT DI KABUPATEN BOYOLALI - HERU IRIANTO; NUNING SETYOWATI (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2009)
The aim of studi "women's labour effusing to enhance productivity and wellbeing of family: Studi at the breeder of dairy cattle in Boyolali District" are to know how many the woman labour effusing at dairy cattle livestock in Boyolali.